ANALISIS TINGKAT PELAYANAN (LEVEL OF SERVICE) PEJALAN KAKI PADA RUAS JALAN DRAMAGA KOTA BOGOR - Mega Khoirul Amri; Eko Wiyono (Politeknik Negeri Jakarta, 2021)
As a result of the high volume of pedestrians around Dramaga Street, Bogor City (in the morning, afternoon, and evening) causing conflicts between pedestrians in the area. These conflicts occur both among pedestrians, and pedestrians with the motor vehicle. This research aims to analyze the pedestrian level of service (LOS), pedestrian characteristics, pedestrian facilities, and develop a pedestrian design applied to these roads. The method used in this study is a survey of pedestrian volume and direct observation of pedestrian characteristics, then analyzed based on the lever of service. The results show that the level of service on this section has LOS (level of service) A to LOS (level of service) B, with the sidewalk segment in front of Bogor Station having the lowest level of service. Based on individual characteristics, there are differences in the speed of each pedestrian. The analysis show facility segment in front of Bogor Station has the most shortcomings/at least according to the regulations. The development of the pedestrian path design follows the regulation of the Minister of Public Works No: 03/PRT/M/2014 and adapts it to the existing conditions. Keywords: Pedestrian Path Design, Pedestrian Facilities, Pedestrian Characteristics, Level of Service.